Copyright and digital academic library development in the UK. (September 2019) - Muir, Adrienne
Reviews the role of copyright in digital academic and research library development in the UK over the last 25 years, drawing on policy documents, legislative reviews and statutes, project documentation and programme syntheses. Finds that copyright-related issues have presented challenges for the development of digital libraries. UK copyright law has been reformed as a result of consultative reviews, but the role of high-level negotiations between stakeholder representatives and the development of model and blanket licences have arguably been more effective in supporting the development of digital libraries. Despite tensions between libraries and publishers, gradual cultural change and the roles played key players such funding councils and high-level representative groups have facilitated progress. The increasing trend towards open licensing presents new roles for libraries as well as challenges and new business opportunities for publishers. Concludes it is unclear what future UK copyright and research policy will be, but it is likely that improved access to academic resources and research will continue, the roles of libraries and publishers will continue to evolve, and new sources of tension and challenges will arise.